Livelihood Strategy of Scavengers in Kendari City - Rati Anggriawati; Syaifudin S. Kasim; Dewi Anggraini (CV. Literasi Indonesia, 2020)
The purpose of this study was to determine the various barriers faced by scavengers in satisfying the needs of family life and livelihood strategies of scavengers in the Final Waste Disposal Site (TPAS) in Kendari City. The research approach used is a qualitative descriptive approach. Informants in this study include the Head of Rukun Tetangga, Kendari City Sanitation Department staffers and 11 scavengers. The results of this study indicate that various barriers faced by scavengers in fulfilling the needs of family life in TPAS in Kendari City are scavengers who do not have their production assets, the difficulty of getting credit under the pattern of livelihoods, lack of alternative livelihoods. The strategies undertaken in fulfilling the life needs of scavenger families in TPAS in Kendari City include active strategies, passive strategies, and network strategies. Active strategy, when fulfilling the needs of life by a person or family by maximizing all the resources and potential possessed by their family. The passive strategy is a survival strategy that is done by minimizing family expenses. While the network strategy is a strategy carried out by utilizing social networks.